Determining and assessing the risks of commercial and recreational complex building projects in developing countries: a survey of experts in Iran. Issue 3 (24th July 2020) - Khosravi, Mojtaba; Sarvari, Hadi; Chan, Daniel W.M.; Cristofaro, Matteo; Chen, Zhen
Abstract : Purpose: As construction of commercial and recreational complex building projects (CRCBPs) is one of the most important issues in many developing countries and requires a very high cost of implementation, it is important to identify and prioritize the risks of such projects. Therefore, the purpose of this study is to identify and rank the risks of CRCBPs by studying the case of the "Hamedanian Memorial, " a CRCBP in Iran. Design/methodology/approach: To pursue this aim, a descriptive-survey method was used. The statistical population of the study consists of 30 experienced experts (consultants, contractors and employers) of the "Hamedanian Memorial" project selected according to the Cochran formula and minimum population census. A questionnaire was used as the data collection tool, administered in all stages of risk identification and evaluation, and was devised by using library and field methods based on the literature and research background, as well as interviewing experts in the risk identification and evaluation stages. Kendall's coefficient of agreement was used to validate the experts' opinions in the risk identification stage. The ranking in qualitative evaluation was done based on the risk intensity and the cumulative risk index. Findings: The results show that the risks are associated with exchange rate fluctuation, inflation fluctuation, access to skilled workers, contractors' claims and foreign threats from international relations. Originality/value: The results and findings of the present study can be of interest to the executives of large commercial, leisure, public and private projects in developing and developed countries; understanding risks can significantly improve the decision-making process of CRCBPs.